Agricultural extension and rural advisory services: What have we learned? What’s next? - Davis, Kristin E.; Makhija, Simrin; Spielman, David J. (International Food Policy Research Institute, 2021)
Agricultural extension provides the critical connection from agricultural innovation and discovery to durable improvements at scale, as farmers and other actors in the rural economy learn, adapt, and innovate with new technologies and practices. However, lack of capacity and performance of agricultural extension in lower- and middle-income countries is an ongoing concern. Research on agricultural extension and advisory services (in short, extension) has been an integral part of the CGIAR Research Program on Policies, Institutions, and Markets (PIM) since its inception. This brief synthesizes key findings from research funded by and linked to PIM from 2012 to 2021, presenting lessons learned and a vision for the future of extension. A list of all PIM-related extension and advisory services research is provided at the end. Designing and implementing effective provision of extension is complex, and efforts to strengthen extension services often fall into a trap of adopting “best practice” blueprint approaches that are not well-tailored to local conditions. An expansive literature examines the promises and pitfalls of common approaches, including training-and-visit extension systems, farmer field schools, and many others (Anderson and Feder 2004; Anderson et al. 2006; Waddington and White 2014; Scoones and Thompson 2009). To understand extension systems and build evidence for what works and where, the “best-fit” framework, a widely recognized approach developed by Birner and colleagues (2009) and adapted by Davis and Spielman (2017), offers a simple impact chain approach (Figure 1). The framework focuses on a defined set of extension service characteristics that affect performance: governance structures and funding; organizational and management capacities and cultures; methods; and community engagement — all of which are subject to external factors such as the environment, agroecological conditions, and farming-system heterogeneity. To enhance extension performance and, ultimately, a wide range of outcomes and impacts, new and innovative interventions can be applied and adapted within this set of extension characteristics.